2009
DOI: 10.1007/s11207-009-9366-1
|View full text |Cite
|
Sign up to set email alerts
|

Small Solar Wind Transients and Their Connection to the Large-Scale Coronal Structure

Abstract: It has been realized for some time that the slow solar wind with its embedded heliospheric current sheet often exhibits complex features suggesting at least partially transient origin. In this paper we investigate the structure of the slow solar wind using the observations by the Wind and STEREO spacecraft during two Carrington rotations (2054 and 2055). These occur at the time of minimum solar activity when the interplanetary medium is dominated by recurrent high-speed streams and large-scale interplanetary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
80
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 40 publications
13
80
0
Order By: Relevance
“…Higginson et al (2017c) have demonstrated that the 3D structure of reconnection-generated magnetic islands in the heliospheric current sheet are consistent with the observations of small-scale flux rope transients in the slow solar wind (Feng et al 2008;Cartwright & Moldwin 2008Kilpua et al 2009;Yu et al 2014). And Janvier et al (2014) have argued that the power-law distribution of the sizes of these small flux rope transients appears compatible with the power-law distributions of magnetic island plasmoids obtained in various reconnection studies (e.g.…”
supporting
confidence: 74%
“…Higginson et al (2017c) have demonstrated that the 3D structure of reconnection-generated magnetic islands in the heliospheric current sheet are consistent with the observations of small-scale flux rope transients in the slow solar wind (Feng et al 2008;Cartwright & Moldwin 2008Kilpua et al 2009;Yu et al 2014). And Janvier et al (2014) have argued that the power-law distribution of the sizes of these small flux rope transients appears compatible with the power-law distributions of magnetic island plasmoids obtained in various reconnection studies (e.g.…”
supporting
confidence: 74%
“…Note that similar transient structures had previously been detected in in-situ measurements alone (e.g. Crooker et al 1996Crooker et al , 2004Kilpua et al 2009). Smaller-scale periodic density structures have recently been detected in high-resolution in-situ measurements (Kepko et al 2016) that could relate to the density structures released into the solar wind at higher frequencies (Viall et al , 2010(Viall et al , 2015.…”
Section: Introductionsupporting
confidence: 76%
“…The slow solar wind is not as well understood as the fast one, for various reasons probably related to its time variability. Its transient nature and its relation with large-scale coronal structures have been revealed from both in situ (e.g., Kilpua et al 2009) and remote-sensing observations (e.g., the blobs of Sheeley et al 1997). As for the coronal sources, the edges of coronal holes (coronal hole boundaries) have been proposed as the location of reconnection between coronal hole (CH) and non-CH magnetic fields, because of the differential rotation between these two kinds of regions (Schwadron et al 2005;Wang & Sheeley 2004).…”
Section: Introductionmentioning
confidence: 99%